2015
DOI: 10.1007/s11738-015-1902-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of exogenous abscisic acid in adapting of ‘Sultana’ grapevine to low-temperature stress

Abstract: Abscisic acid (ABA) has a key role in some plant species under low-temperature stress (LTS). In this study the effects of ABA at four concentrations (0, 50, 100 and 200 lL) on electrolyte leakage (EL), visual damage index, soluble carbohydrate, proline, total phenolic compound and relative water content (RWC) of leaves of 'Sultana' grapevines were studied under LTS (0, 4 and -4°C). Moreover, to further elucidate the efficiency of foliar ABA on freezing tolerance, some relevant morphophysiological changes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…Ample evidence supports the regulatory role of ABA in conferring tolerance to environmental stresses3339. Here, we found that exogenous pre-treatment with ABA efficiently ameliorated cold-induced oxidative damage, characterized by decreased electrolyte leakage, reduced MDA content, and decreased ROS accumulation (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Ample evidence supports the regulatory role of ABA in conferring tolerance to environmental stresses3339. Here, we found that exogenous pre-treatment with ABA efficiently ameliorated cold-induced oxidative damage, characterized by decreased electrolyte leakage, reduced MDA content, and decreased ROS accumulation (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…A previous study showed that exogenous ABA application before the onset of cold stress improved cold resistance of plants33. ABA can improve the antioxidant defense system, thus protecting plant cells from damage caused by over-accumulated ROS34.…”
mentioning
confidence: 94%
“…Both NO and ABA are involved in many botanic physiological and stress‐resistance processes . Low temperature could induce endogenous NO and ABA production to relieve chilling injury symptoms of fruit during storage . Firmness is an important quality factor in many fruits, and the decrease in firmness during storage is primarily due to the destruction of cell wall structure and the depolymerization of pectin, which are catalyzed by the action of polygalacturonase and pectin methylesterase .…”
Section: Discussionmentioning
confidence: 99%
“…Many recent studies have indicated that cold can induce the generation of endogenous NO or ABA, which in turn contribute to the alleviation of chilling injury symptoms via regulating antioxidative metabolism in fruit . These studies have shown that changes in endogenous NO or ABA have certain degrees of specificity under cold stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation